Understanding career decision-making: influencing factors and application of Krumboltz's social learning theory - Mohd Yunus, Noordiyana; Zainudin, Zaida Nor; Mohamad Yusop, Yusni; Wan Othman, Wan Norhayati; Engku Kamarudin, Engku Mardiah; Anuar, Muharram (Human Resources Management Academic Research Society, 2024)
Krumboltz Social Learning Theory is a career counselling theory which believes learning experiences are influencing the career decision making process. This article is a systematic review study, which explores the influencing factors in people career choices, the application of Krumboltz Social Learning Theory in career counselling and the chance event and skills included in the extension of this theory. Electronic database was used to search related reading materials and a total of 10 journals were found. The influencing factors in career decision making process are genetic endowment and special abilities, environmental conditions and events, learning experiences and task approached skills. The findings of this review discuss Krumboltz's Social Learning Theory of career decision making presents a nuanced framework that acknowledges the multifaceted nature of career choices. It emphasizes the role of both inherent and environmental factors in shaping career decisions. The Krumboltz Social Learning Theory can be applied to the various cases for career counselling such as with gifted students, disabilities and nurses burn-out. The chance event gives significant value to the career development and Planned Happenstance Theory provide five skills (curiosity, persistence, flexibility, optimism and risk taking) to response to the event. The results of this review are helpful for counselors and other mental health professionals who interact with families and students. Therapists can use these findings to help their clients create therapy plans that take into account the significance of choosing a career path well.